Peran Perceived Influencer Terhadap Intention to Purchase Recommended Brands - Virra Aprillian; Nina Nurhasanah (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to investigate the role of influencers as effective tools in providing brand recommendations and their influence on followers in shaping perceptions and behaviors towards endorsed brands. The study was conducted among TikTok users in Jakarta with a total of 150 respondents. The research employed a quantitative approach with the SEM Lisrel analysis method. The findings of this study revealed several important findings. First, it was found that perceived influence (PI) has a positive influence on brand engagement in self-concept (BESC), indicating that influencer influence can affect user engagement with brands in the context of their self-concept. Second, no positive relationship was found between perceived influence (PI) and brand expected value (BEV), suggesting that influencer influence does not necessarily impact positive evaluations of brand value. Third, brand engagement in self-concept (BESC) has a positive influence on intention to purchase recommended brands (IP), indicating that user engagement with brands contributes to the intention to purchase recommended brands. Furthermore, it was found that perceived influence (PI) has a positive influence on intention to purchase recommended brands (IP), reaffirming that influencer influence can drive the intention to purchase recommended brands. Finally, brand expected value (BEV) has a positive influence on intention to purchase recommended brands (IP), indicating that the expected value of a brand contributes to the intention to purchase recommended brands. This study provides insights into the importance of the influencer role in shaping user perceptions and behaviors towards brands and its implications for the intention to purchase recommended brands.